2011
DOI: 10.1088/2040-8978/14/1/015002
|View full text |Cite
|
Sign up to set email alerts
|

All-angle self-collimation in two-dimensional rhombic-lattice photonic crystals

Abstract: In this work, the self-collimating phenomenon in two-dimensional rhombic-lattice photonic crystals is discussed in detail. The equi-frequency contours of a rhombic-lattice rod-type photonic crystal structure are calculated with the plane wave expansion method for different lattice angles and rod radii. A broad range of flat and open equi-frequency contours is found. A rhombic-lattice photonic crystal made of 301 × 21 silicon rods (n = 3.5) in air is presented as an illustration to demonstrate the broadband all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…They went on to exploit this PC to build waveguides without a physical channel, optical interconnects, beam splitters, Mach-Zender interferometers, a two-bit all-optical analog-to-digital converter and more [39]-all these devices consist only of the self-collimating PC and some mirrors constructed by locally modifying hole radii. Over time, more sophisticated examples have been proposed and demonstrated: very recently, Z. H. Wu et al proposed a PC for which k y is nearly independent of k x over the entire Brillouin zone, leading to selfcollimation for a very broad range of incident angles [40].…”
Section: Self-collimationmentioning
confidence: 99%
See 1 more Smart Citation
“…They went on to exploit this PC to build waveguides without a physical channel, optical interconnects, beam splitters, Mach-Zender interferometers, a two-bit all-optical analog-to-digital converter and more [39]-all these devices consist only of the self-collimating PC and some mirrors constructed by locally modifying hole radii. Over time, more sophisticated examples have been proposed and demonstrated: very recently, Z. H. Wu et al proposed a PC for which k y is nearly independent of k x over the entire Brillouin zone, leading to selfcollimation for a very broad range of incident angles [40].…”
Section: Self-collimationmentioning
confidence: 99%
“…(1.13). The matrix Z Fallahi that Fallahi and Hafner call their impedance matrix has half the dimensions of R. It is defined such that 40) for V and I (i.e. vectors of E and H grating order amplitudes) due to only forward modes in a semi-infinite PC.…”
Section: Multiconductor Transmission Line Definitionmentioning
confidence: 99%
“…These three characteristics can greatly enhance the efficiency of the SC and extend its applications [14]. Notice that most of the works reported so far support only one special polarization for the all-angle and broad-band SC, or the all-angle polarization insensitivity is limited to some frequency ranges only [2,11,14,15,22,23,[37][38][39][40][41][42][43][44]. To the best of our knowledge, there have been no reports on the all-angle, polarization-insensitive and, at the same time, relatively broad-band SC.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier experimental and theoretical studies of the PCs have focused on photonic band gaps and several appropriate devices have already been developed [3]. But in the recent years, the studies have revealed that the photonic bands show unusual dispersion properties, which make them sources of several attractive effects [4,5] such as negative refraction and left handedness [6][7][8], super-prism [9], slow light [10] and SC [2,[11][12][13][14][15][16][17][18][19] effects. Among these, the SC in PCs provides a brand new way of confining light propagation, which is different from conventional PC waveguides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation